Irreversible order-disorder transformation of Ge(0 0 1) probed by scanning tunnelling microscopy. (29th September 2015) - Persichetti, L; Sgarlata, A; Fanfoni, M; Balzarotti, A
Abstract: We investigate the surface structure of Ge(0 0 1) during the (2 × 1)–(1 × 1) phase transition occurring at T > 1130 K by high-resolution scanning tunnelling microscopy. We find a drastic size reduction of dimerized domains in line with substantial dimer breakup accompanied by surface roughening. Completing the picture provided by previous spectroscopic observations, probing with high spatial resolution reveals the nucleation of several nanodomains with distinct vicinal orientations and reconstructions. The structural transformation is irreversible and is not observed for other singular faces of Ge.